Deciphering the impact of nitrogen morphologies distribution on nitrogen and biomass accumulation in tobacco plants - Li, Shichen; Jiang, Tao; Ahmed, Waqar; Yang, Yingfen; Yang, Linyuan; Zhang, Tao; Mei, Fupeng; Alharbi, Sulaiman Ali; Shan, Qu; Guo, Cuilian; Zhao, Zhengxiong (Frontiers in Plant Science, 2024)
Background and aims: Nitrogen (N) distribution in plants is intricately linked to key physiological functions, including respiration, photosynthesis, structural development, and nitrogen storage. However, the specific effects of different N morphologies on N accumulation and plant growth are poorly understood. Our research specifically focused on determining how different N morphologies affect N absorption and biomass accumulation. Methods: This study elucidated the impact of different application rates (CK: 0 g N/plant; T1: 4 g N/plant; T2: 8 g N/plant) of N fertilizer on N and biomass accumulation in tobacco cultivars Hongda and K326 at different growth stages. Results: Our findings emphasize the critical role of N distribution in various plant parts, including leaves, stems, and roots, in determining the complex mechanisms of N and biomass accumulation in tobacco. We found that in relation to total N, a greater ratio of water-soluble N (Nw) in the leaves facilitated N accumulation in the leaves. In contrast, an increased ratio of SDS (detergent)insoluble N (Nin-SDS) in the leaves and non-protein N (Nnp) in the roots hindered this increase. Additionally, our results indicate that a greater proportion of Nnp in leaves has a negative impact on biomass accumulation in the leaves. Furthermore, elevated levels of Nin-SDS, Nw, and Nnp in the roots, and Nnp in the leaves adversely affected biomass accumulation in tobacco leaves. The Hongda cultivar exhibited greater biomass and N accumulation abilities as compared to K326. Conclusions: Our findings highlight the significant role of distribution of N morphologies on plant growth, as well as N and biomass accumulation in tobacco plants. Understanding N distribution allows farmers to optimize N application, minimizing environmental losses and maximizing yield for specific cultivars. These insights advance sustainable agriculture by promoting efficient resource use and reducing environmental impact.